Numerical simulation and experiment of grain motion in the conveying system of ratooning rice harvesting machine - Liu, Weijian; Luo, Xiwen; Zeng, Shan; Zang, Ying; Wen, Zhiqiang; Zeng, Li; Gu, Wei (International Journal of Agricultural and Biological Engineering, 2022)
The mixtures, grains, and residues in the ratooning rice harvesting machine need to be conveyed forward, backward, upward, and downward. Due to such operations, often accumulation and blockage take place at the intersection of a horizontal-vertical screw conveyor, resulting in low efficiency, high power consumption, and even grain damage. In this study, a CFD-DEM approach was applied to address the above problems. Firstly, a pneumatic conveying device was designed for ratooning rice, and then the motion of the rice grains and airflow field was analyzed in detail. The effects of different cross-sectional heights and lengths of the contraction section related to the mixing cavity were examined. Finally, the three-factor quadratic regression orthogonal rotational combination method was adopted in the experiment, and the fan velocity, filling coefficient, and speed of the horizontal screw conveyor were taken as test factors. The results showed that with the increasing cross-sectional height of the contraction section in the mixing cavity, the grain velocity decreased and the dispersity increased. With increasing length of the contraction section in the mixing cavity, the area of the high-speed airflow zone increased and the diffusion effect was enhanced. At the fan velocity of 2700 r/min, the filling coefficient was 0.41, the speed of the horizontal screw conveyor was 1173 r/min, and the outlet flow optimization index was the highest, which was 45.9% higher than that obtained without airflow.Keywords: ratooning rice, screw conveyor, grain motion, harvesting machine, CFD-DEMDOI: 10.25165/j.ijabe.20221504.6681Citation: Liu W J, Luo X W, Zeng S, Zang Y, Wen Z Q, Zeng L, et al. Numerical simulation and experiment of grain motion in the conveying system of ratooning rice harvesting machine. Int J Agric & Biol Eng, 2022; 15(4): 103–115.